Actio Pauliana in Bankruptcy Cases and Their Legal Effects (Case Study of Supreme Court Decision No. 388 K/Pdt.Sus-Pailit/2014): Actio Pauliana dalam Perkara Kepailitan dan Akibat Hukumnya (Studi Kasus Putusan Mahkamah Agung No. 388 K/Pdt.Sus-Pailit/2014) - Romadhan, Moh Rahmat Rizki; Suprapti, Duhita Driyah (Faculty of Law, Universitas Negeri Semarang, 2024)
This research delves into the Actio Pauliana in bankruptcy cases, which involves legal action taken prior to declaring bankruptcy against the Debtor. The method employed in this research is a qualitative approach, utilizing statutory regulations and case studies. This type of research is normative juridical, examining and analyzing Supreme Court Decision No. 388 K/Pdt.Sus-Pailit/2014, the Civil Code, Law No.37/2004, Law no. 40/2007, and interviews with bankruptcy experts. Primary data sources include interviews with bankruptcy experts, while secondary data sources consist of primary legal materials such as legislation and court decisions, along with secondary legal materials like books, journals, and articles related to the research, as well as tertiary legal materials. Researchers gathered legal analysis materials and conducted literature studies, which were discussed qualitatively and descriptively. The discussion in this research revolves around the legal act of transferring company assets through a sale, executed under the name of the President Director before the court's decision to declare bankruptcy, as well as the legal consequences of the sale and purchase agreement, and the examination of evidence regarding the actions of the main director.